2021
DOI: 10.1111/tbed.14053
|View full text |Cite
|
Sign up to set email alerts
|

Absence of proteinase K‐resistant PrP in Korean Holstein cattle carrying potential bovine spongiform encephalopathy‐related E211K somatic mutation

Abstract: Bovine spongiform encephalopathy (BSE) is a kind of prion disease caused by proteinase K‐resistant prion protein (PrPSc) in cattle. Although BSE has been reported worldwide, BSE‐infected cases have never been reported in Korea. In a previous study, we identified BSE‐related somatic mutation E211K in 3 Korean Holstein cattle. In Korea, the BSE surveillance system has been established. However, several genetic factors have not been controlled simultaneously thus far. In the present study, we performed enhanced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…Prion diseases are fatal and infectious neurodegenerative disorders caused by the misfolded toxic form of prion protein (PrP Sc ) originating from a benign form of prion protein (PrP C ). Although the conversion process of PrP C to PrP Sc is still unclear, several factors that play a pivotal role in the conversion have been identified thus far (1)(2)(3)(4)(5). Among these factors, previous studies have reported that the shadow of prion protein (Sho) interacts with prion protein (PrP) and accelerates the conversion of PrP C to PrP Sc (6).…”
Section: Introductionmentioning
confidence: 99%
“…Prion diseases are fatal and infectious neurodegenerative disorders caused by the misfolded toxic form of prion protein (PrP Sc ) originating from a benign form of prion protein (PrP C ). Although the conversion process of PrP C to PrP Sc is still unclear, several factors that play a pivotal role in the conversion have been identified thus far (1)(2)(3)(4)(5). Among these factors, previous studies have reported that the shadow of prion protein (Sho) interacts with prion protein (PrP) and accelerates the conversion of PrP C to PrP Sc (6).…”
Section: Introductionmentioning
confidence: 99%
“…The animals did not show any clinical and histopathological features. Detailed information regarding the tested animals was presented in a previous study (Y. C. Kim et al., 2022; Won et al., 2020). The Tg( PRNP )1896Pcg/FVB mice carrying bovine PRNP gene (GenBank ID: AJ298878) were obtained from the Jackson laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we carried out an in-depth examination on PrP Sc by using enzyme immunoassay (EIA), RT-QuIC and PMCA in three Holstein cattle carrying the E211K somatic mutation of the bovine PRNP gene. Kim et al, 2022;Won et al, 2020). The Tg(PRNP)1896Pcg/FVB mice carrying bovine PRNP gene (GenBank ID: AJ298878) were obtained from the Jackson laboratory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prion diseases are infectious brain proteinopathies caused by a pathogenic form of prion protein (PrP Sc ) converted from an endogenous form of prion protein (PrP C ) and are classified into several types in a wide range of mammalian hosts: Creutzfeldt-Jakob disease (CJD), fatal familial insomnia (FFI) and Gerstmann-Sträussler-Scheinker syndrome (GSS) in humans; scrapie in sheep and goats; bovine spongiform encephalopathy (BSE) in cattle; and chronic wasting disease (CWD) in the Cervidae family (1)(2)(3)(4)(5)(6)(7). After CWD was first reported in mule deer in the USA in the 1967, CWD has been reported globally, including in North America, South Korea and Scandinavia, in variable cervid species, such as white-tailed deer, elk, moose, red deer and reindeer (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%